Kazakhstan : Public Expenditure Review, Volume 2. Main Report - World Bank (Washington, DC, 2013)
The report is the public expenditure review for Kazakhstan, and builds upon previous work on the country's transition experience to a market-oriented economy, and of recent public sector reforms. It comprises three volumes, namely, the Summary Report, the Main Report, and Annexes and Statistical Appendix, aiming at identifying key public expenditure issues, suggesting also, possible strategies, and policy options. Although the country achieved significant progress in liberalizing, and stabilizing the economy, including implementing institutional reforms to discipline public expenditures, outstanding issues remain, particularly regarding the persistent fiscal imbalance, the deficient domestic resource mobilization management, unreliable expenditure prioritization, and inefficient budgetary execution. The report suggests strategy options, and policy reforms that should, through a programmed deficit reduction, attain fiscal sustainability. These options address: the rationalization of domestic resource mobilization, mainly oil/gas rents to preserve domestic savings, capital, and development of non-oil sectors; the need for governmental action on program priority, such as budgeting, and performance evaluation; strengthening intergovernmental relations, through improved fiscal decentralization, increased local accountability, and tax reforms; and, creating the initiative for private participation.